2011
DOI: 10.1190/1.3564954
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fluid substitution in a porous and fractured medium

Abstract: To improve quantitative interpretation of seismic data, we analyze the effect of fluid substitution in a porous and fractured medium on elastic properties and reflection coefficients. This analysis uses closed-form expressions suitable for fluid substitution in transversely isotropic media with a horizontal symmetry axis (HTI). For the HTI medium, the effect of changing porosity and water saturation on (1) P-wave moduli, (2) horizontal and vertical velocities, (3) anisotropic parameters, and (4) reflection coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…It can be seen that as the effective isotropic background rock property (in this case as a result of changing water saturation) changes, this has an effect on the anisotropy of the fractured rock, a result which may not be obvious. A similar observation was made in the numerical study (although dispersion was not considered) by Sil et al (2011) where they showed that changes in the isotropic background properties as a result of changes in water saturation and porosity had an effect on P-wave anisotropy of the fractured rock considered. It then follows that if the effective isotropic background property is frequency dependent, then the effect on P-wave anisotropy would be frequency dependent.…”
Section: O D E L L I N G I N S I G H T a N D Discussion Ssupporting
confidence: 76%
“…It can be seen that as the effective isotropic background rock property (in this case as a result of changing water saturation) changes, this has an effect on the anisotropy of the fractured rock, a result which may not be obvious. A similar observation was made in the numerical study (although dispersion was not considered) by Sil et al (2011) where they showed that changes in the isotropic background properties as a result of changes in water saturation and porosity had an effect on P-wave anisotropy of the fractured rock considered. It then follows that if the effective isotropic background property is frequency dependent, then the effect on P-wave anisotropy would be frequency dependent.…”
Section: O D E L L I N G I N S I G H T a N D Discussion Ssupporting
confidence: 76%
“…In this paper, we extend the linearized AVO and poroelasticity proposed by Russell et al (2011) to the case of linearized AVOA and anisotropic poroelasticity. Gassmann's (1951) equations formulated the effects of fluid properties on seismic response, and Gurevich (2003) studied the elastic properties of saturated porous rocks permeated with aligned vertical fractures incorporating anisotropic Gassmann's equation and linear-slip model (Sil, Sen and Gurevich 2011). Huang et al (2015) derived analogical expressions for anisotropic fluid substitution in fracture-induced media.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the pennyshaped fracture model assumption, Gurevich [13] combined the anisotropic Gassmann's [12] equation with the more generally linear-slip (LS) theory to propose a saturated fractured porous model, who derived the exact analytical expressions for the stiffness matrix of a fluid-saturated fractured porous rock, related to the dry elastic properties of isotropic background, matrix moduli, porosity, dry fracture compliances, and saturated fluid modulus. On this basis, Sil et al [14] and Huang et al [15] analyzed the effects of fluid substitution on elastic properties and reflection coefficients in saturated fractured porous media with HTI symmetry and orthorhombic symmetry, respectively. Using the anisotropic Gassmann equation and the linear-slip theory model, Pan and Zhang [16] derived the weakly anisotropic approximations of fluid substitutions and reflection coefficients for a set of parallel, aligned vertical fractures (i.e., an equivalent HTI medium) and two sets of orthogonal vertical fractures (i.e., an equivalent orthorhombic medium), respectively.…”
Section: Introductionmentioning
confidence: 99%